Decisive evidence corroborates a null relationship between MTHFR C677T and chronic kidney disease: A case–control study and a meta-analysis. Issue 29 (17th July 2020) - Chang, Hsueh-Lu; Chen, Guei-Rung; Hsiao, Po-Jen; Chiu, Chih-Chien; Tai, Ming-Cheng; Kao, Chung-Cheng; Tsai, Dung-Jang; Su, Hao; Chen, Yu-Hsuan; Chen, Wei-Teing; Su, Sui-Lung
Abstract: Background: Previous meta-analyses have explored the association between the C677T polymorphism of methyltetrahydrofolate reductase ( MTHFR) and chronic kidney disease (CKD) but there were no studies with a decisive conclusion. Furthermore, the high heterogeneity among different populations is not yet interpreted. Objectives: This study used trial sequential analysis (TSA) to evaluate whether the nowadays conclusion supported by current cumulative samples. We also applied case-weighted meta-regression to explore the potential gene–environment interactions. Methods: For the first stage of this study we conducted a case–control study involving 847 dialysis patients from 7 hemodialysis centers in Taipei during 2015 to 2018 and 755 normal controls from a health center in the Tri-Service General Hospital. The second stage combined the results from the first stage with previous studies. The previous studies were collected from PubMed, EMBASE, and Web of Science databases before January 2018. Results: From the case–control study, the T allele of MTHFR C677T appeared to have a protective effect on end-stage renal disease compared with the C allele [odds ratio (OR): 0.80, 95% CI (confidence interval) = 0.69–0.93]. However, the meta-analysis contradicted the results in Asian (OR = 1.12, 95% CI = 0.96–1.30). The same analysis was also applied in Caucasian and presented similar results from Asian (OR = 1.18, 95% CI = 0.98–1.42). The TSA showed our case–control study to be the decisive sample leading to a null association among Asian population. The high heterogeneity (I 2  = 75%) could explain the contradictory results between the case–control study and the meta-analysis. However, further case-weighted meta-regression did not find any significant interaction between measured factors and MTHFR C677T on CKD. Conclusions: High heterogeneities were found in both Caucasian and Asian, which caused the null relationship in meta-analysis while there were significant effects in individual studies. Future studies should further explore the high heterogeneity that might be hidden in unmeasured gene–environment interactions, to explain the diverse findings among different populations. Abstract : Supplemental Digital Content is available in the text